Caenorhabditis elegans as a model system for human diseases. (June 2020) - Markaki, Maria; Tavernarakis, Nektarios
Graphical abstract: Highlights: C. elegans offers a powerful platform to emulate key aspects of human pathology. Focus on C. elegans models of the most common neurodegenerative disorders. Worm models have provided critical insights into mechanisms underlying disease. Unravelling disease pathogenesis identifies novel candidate therapeutic targets. Evolutionary conservation between C. elegans and humans offers in vivo target validation. Abstract : The nematode Caenorhabditis elegans offers unique advantages that enable a comprehensive delineation of the cellular and molecular mechanisms underlying devastating human pathologies such as stroke, ischemia and age-associated neurodegenerative disorders. Genetic models of human diseases that closely simulate several disease-related phenotypes have been established in the worm. These models allow the implementation of multidisciplinary approaches, in addition to large-scale genetic and pharmacological screenings, designed to elucidate the molecular mechanisms mediating pathogenesis and to identify targets and drugs for emergent therapeutic interventions. Such strategies have already provided valuable insights, highly relevant to human health and quality of life. This article considers the potential of C. elegans as a versatile platform for systematic dissection of the molecular basis of human disease, focusing on neurodegenerative disorders.